Evaluating Social Protection Policies With an Implementation Science Framework: India's Direct Benefit Transfer for Tuberculosis; Comment on "Does Direct Benefit Transfer Improve Outcomes Among People With Tuberculosis? - A Mixed-Methods Study on the Need for a Review of the Cash Transfer Policy in India" - Ann M. Schraufnagel; Priya Shete (Kerman University of Medical Sciences, 2023)
Addressing the social and structural determinants of tuberculosis (TB) through social protection programs is a central feature of global public health policy and disease elimination strategies. However, how best to implement such programs remains unknown. India's direct benefit transfer (DBT) program is the largest cash transfer program in the world dedicated to supporting individuals affected by TB. Despite several studies aimed at evaluating the impact of DBT, many questions remain about its implementation, mechanisms of action, and effectiveness. Dave and Rupani's mixed-methods evaluation of this program previously published in this journal offers valuable insights into the strengths and limitations of the DBT program in improving TB treatment outcomes. Their results also provide an opportunity for demonstrating how systematically collected data may be further analyzed and presented using implementation science, a field of study using methods to promote the systematic uptake of evidence-based interventions to support sustainable program scale-up.